A Mobile Agent Based Secure Aggregation in Sensor Network - Kumar, Neeraj; Patel, R. B. (INFOCOMP Journal of Computer Science, 2010)
Compared with traditional wired and wireless networks, low-power wireless sensor networks (WSN) can be rapidly deployed in a large geographical area in a self-configured manner. In such types of networks data aggregation is a key issue. Hop-by-hop data aggregation in this regard is a very important technique for reducing the communication overhead and energy expenditure of sensor nodes during the process of data collection in a sensor network. However, because individual sensor readings are lost in the per-hop aggregation process, compromised nodes in the network may forge false values as the aggregation results of other nodes, resulting the base station into accepting wrong aggregation results. Here a fundamental challenge is how the base station can obtain a good approximation of the aggregated data when a group of sensor nodes are compromised. In this paper, we have designed and implemented a prototype for secure data aggregation using mobile agent (MA) technology. The key advantage of using MA is their capability to move in heterogeneous networks without consuming many resources. The designed scheme uses a novel probabilistic grouping technique to dynamically partition the nodes in a tree topology into multiple logical levels of similar sizes. A commitment-based hop-by-hop aggregation is performed by MA in each group to generate a group aggregate. Extensive analysis and simulations show that designed scheme can achieve the level of efficiency close to an ordinary hop-by-hop aggregation protocol while providing high assuranceon the trustworthiness of the aggregation result. The prototype implementation on top of TinyOS shows that designed scheme is practical on current sensor nodes such as Mica2 motes